The solution to the conjunction -5 ≤ 3m + 1 < 4 is m ≥ -2 and m < 1.
To solve the conjunction -5 ≤ 3m + 1 < 4, we need to solve the two inequalities separately. Starting with the left inequality: -5 ≤ 3m + 1. We subtract 1 from both sides: -6 ≤ 3m. Dividing both sides by 3, we get: -2 ≤ m. Next, we solve the right inequality: 3m + 1 < 4. We subtract 1 from both sides: 3m < 3. Dividing both sides by 3, we get: m < 1. Therefore, the solution to the conjunction is m ≥ -2 and m < 1. This means that m is greater than or equal to -2, but less than 1.
#SPJ2
B.There are vertical asymptotes at -5/2 & 0 and a hole at 3.
C.There is a vertical asymptote at 3 and a hole at 0.
D.There are vertical asymptotes at 0 & 3
Answer:
We factor the function
f(x)= [ (2x + 5)(x-3) ]/[ 4x(x-3) ], x ≠ 3
f(x)= [ (2x + 5) ]/[ 4x ], x ≠ 3
A full cancellation of a denominator factor means that there will be a hole. The answer is that there is a vertical asymptote at 0 and a hole at 3.
Step-by-step explanation:
She reacts to what the animals say.
B.
She makes comments to the animals.
C.
She asks the animals questions.
D.
She tells Lurvy about the animals talking.
Answer:
4 cups that's how many cups Jerry ate
A.
He will be approved for a car loan with a low interest rate.
B.
His application for a new credit card will be denied.
C.
He will pay a high rate for a mortgage.
D.
He will have a low credit score.
Answer: 4/7
Step-by-step explanation:
Como está reduciendo fracciones, divide por el factor más grande, que es doce. 48/12 84/12 = 4/7
Espero que esto te ayude y que tengas un día maravilloso. ¡¡Buena suerte!!
Answer:
−15x+−30
Step-by-step explanation:
Distribute:
=7+(−3)(5x)+(−3)(−10)+−67
=7+−15x+30+−67
Combine Like Terms:
=7+−15x+30+−67
=(−15x)+(7+30+−67)
=−15x+−30
Answer:
Step-by-step explanation:
66